Digital Leadership Strategy for Technology-Driven Sustainable Business Transformation - Sunarya, Po Abas; Rahardja, Untung; Yusup, Muhamad; Mardiana, Mardiana; Sari, Meri Mayang; Kamal, ⁠Abdullah Arif (Technomedia Journal, 2025)
The digital era demands organizations to adapt through sustainable business transformation that combines technological innovation and sustainability values. Digital leadership plays a crucial role in building an adaptive culture, driving innovation, and utilizing technology as a business strategy. This study aims to explore digital leadership strategies in supporting technology-driven business transformation aligned with the Sustainable Development Goals (SDGs). The method used is a literature review and case study analysis of leading companies like Amazon, Tesla, and Gojek that have successfully undergone digital transformation. The focus of the research includes leadership vision, the utilization of technologies such as Artificial Intelligence (AI), Big Data, and IoT, as well as the integration of sustainability principles through the Environmental, Social, and Governance (ESG) framework. The findings show that a clear vision, mastery of technology, and commitment to sustainability are key factors for successful transformation, while also providing strategic insights for organizations in formulating relevant, competitive, and sustainable digital strategies. In order to achieve SDG goals, this study also highlights the importance of cross-sector collaboration and the use of technology to create positive social impacts.